INFLUENCE OF DEFORMATION IN THE LINE OF WIRE MILL 150 ON DISPERSION OF PEARLITE OF STEEL 80K - V. A. Lutsenko; P. A. Bobkov; O. V. Lutsenko; T. N. Golubenko; V. V. Gordiyenko (Литьë и металлургия)
Peculiarities of formation and distribution of pearlitic structure of steel 80K in a blank and after deformation in various areas of wire mill (in semi-finished rolled products and rolled wire) are established. It is shown that irregularity of temperature field by the section of semi-finished rolled products influences on processes of structure formation. It is shown by researches that the increase of deformation degree and the subsequent controlled accelerated cooling in the line of wire mill 150 leads to increase in uniformity of pearlitic structure and its dispersion.